1z-16=14z-68

Simple and best practice solution for 1z-16=14z-68 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1z-16=14z-68 equation:


Simplifying
1z + -16 = 14z + -68

Reorder the terms:
-16 + 1z = 14z + -68

Reorder the terms:
-16 + 1z = -68 + 14z

Solving
-16 + 1z = -68 + 14z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-14z' to each side of the equation.
-16 + 1z + -14z = -68 + 14z + -14z

Combine like terms: 1z + -14z = -13z
-16 + -13z = -68 + 14z + -14z

Combine like terms: 14z + -14z = 0
-16 + -13z = -68 + 0
-16 + -13z = -68

Add '16' to each side of the equation.
-16 + 16 + -13z = -68 + 16

Combine like terms: -16 + 16 = 0
0 + -13z = -68 + 16
-13z = -68 + 16

Combine like terms: -68 + 16 = -52
-13z = -52

Divide each side by '-13'.
z = 4

Simplifying
z = 4

See similar equations:

| 7+33=-4(2x-10) | | X+5-x=4x-1-x | | 2(5)-8y=10 | | 7+-2t=-56+5t | | -3(x-1)=-4x+6 | | 3(5c-1)-1=12c+2 | | Y=x(x)-7 | | 3-49=7 | | 10x+9y+8z=175 | | -3(-5)+10x=-5 | | 5x-2-3x=5+x-7 | | 1.4x=-14 | | 3(2-x)=5-x | | -7(x+8)-44=4-69 | | Nx+m=p | | f(x)=7x-19f(-10) | | 15x-7=14x-12 | | 3x-3=-2-x | | X+20+2x=-16-2x-19 | | -2x+4=2x-1-3x | | 2(3x-4)-12=5(x-3) | | -0.6x+0.7x+9=-1 | | -2(3-x)+1=4(x-1)-3 | | A=47.5+-0.5*9 | | 59+44t=19t-39 | | 3x+44=8x-6 | | 8y=3(y-5) | | 4x-5=9x-7 | | X^3-3x^2-104x+216=0 | | 2x+3=9x-7 | | 2(0)=3y-13 | | e^6x=55e^9x |

Equations solver categories